Confidence intervals for proportions and related measures of effect size - Newcombe, Robert G. (Boca Raton CRC Press, Taylor & Francis Group, 2013)
Addressed primarily at researchers who have not been trained as statisticians, this book describes how to use appropriate methods to calculate confidence intervals to present research findings. It covers background issues, such as the link between hypothesis tests and confidence intervals and why it is usually preferable to report the latter. Chapters begin with the simplest cases of a mean or a proportion based on a single sample and then move on to more complex applications. Although the books illustrative examples are mainly health-related, the methods described can also be applied to research in a wide range of disciplines.
Includes bibliographical references (p. 401-419) and index.
Keywords: Biometry -- methods; Data Interpretation, Statistical